Review of the plant bug tribe Eccritotarsini (Hemiptera: Heteroptera: Miridae) of India and Sri Lanka with description of two new genera and six new species - Yeshwanth, H.M.; Konstantinov, Fedor V. (European Journal of Taxonomy, 2021)
The fauna of the bryocorine plant bug tribe Eccritotarsini from India and Sri Lanka is reviewed and updated. Ten genera and 20 species are reported from the region including two genera and six species described as new: Harpedona vittlaensis sp. nov., Lopidolon dandeliensis sp. nov., Mertila rubrocephala sp. nov., Namyatovia gen. nov. for N. castlerockensis gen. et sp. nov. (as the type species) and N. sirsiensis gen. et sp. nov., and Stonedahlia gen. nov. for S. mishmiensis gen. et sp. nov. The genus Bromeliaemiris Schumacher, 1919 is synonymized with Lopidolon Poppius, 1911. Dioclerus lutheri (Poppius, 1912) and Ernestinus ramkeshariae Yasunaga & Ishikawa, 2016 are reported from India for the first time. Differential diagnoses, keys, habitus photographs, illustrations of male genitalic structures, host and distributional information are provided for all genera and species.